Single-dose psilocybin for a treatment-resistant episode of major depression: Impact on patient-reported depression severity, anxiety, function, and quality of life - Goodwin, Guy M; Aaronson, Scott T; Alvarez, Oscar; Atli, Merve; Bennett, James C; Croal, Megan; DeBattista, Charles; Dunlop, Boadie W; Feifel, David; Hellerstein, David J; Husain, Muhammad Ishrat; Kelly, John R; et al. (Journal of affective disorders, 2023)
BACKGROUND: COMP360 is a proprietary, synthetic formulation of psilocybin being developed for treatment-resistant depression (TRD), a burdensome, life-threatening illness with high global impact. Here, we expand upon the previous report of primary outcomes from a phase 2 study of COMP360 in individuals with TRD-the largest randomised controlled clinical trial of psilocybin-to discuss findings of the exploratory efficacy endpoints. METHODS: In this phase 2, double-blind trial, 233 participants with TRD were randomised to receive a single dose of psilocybin 25 mg, 10 mg, or 1 mg (control), administered alongside psychological support from trained therapists. Efficacy measures assessed patient-reported depression severity, anxiety, positive and negative affect, functioning and associated disability, quality of life, and cognitive function. RESULTS: At Week 3, psilocybin 25 mg, compared with 1 mg, was associated with greater improvements from Baseline total scores in all measures. The 10 mg dose produced smaller effects across these measures. LIMITATIONS: Interpretation of this trial is limited by the absence of an active comparator and the possibility of functional unblinding in participants who received a low dose of psilocybin. CONCLUSIONS: Three weeks after dosing, psilocybin 25 mg and, to a lesser degree, 10 mg improved measures of patient-reported depression severity, anxiety, affect, and functioning. These results extend the primary findings from the largest randomised clinical trial of psilocybin for TRD to examine other outcomes that are of importance to patients.
Keywords: Treatment-resistant depression; depresivní porucha unipolární; Depressive Disorder, Major; Patient-reported outcomes; úzkost; kvalita života; psilocybin; Antidepressant; hodnocení výsledků péče pacientem; lidé; Quality of Life; deprese; Depression; Patient Reported Outcome Measures; Humans; Anxiety; Psychedelic; Psilocybin